2015
DOI: 10.14393/bj-v31n3a2015-26093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant regulators on the growth and flowering of Saint Augustine grass plants

Abstract: ABSTRACT:The objective of this work was to evaluate the effects of three plant growth inhibitors on the development and emission of floral rachis of Saint Augustine grass [Stenotaphrum secundatum (Walt.) Kuntzel] plants. The study was carried out in a 15 month old lawn with the experimental plots being distributed in accordance with a complete randomized block design with four replications. The treatments consisted of sole application of trinexapac-ethyl (113, 226, 452, 678, and 904 g ai ha -1 ), prohexadione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…In a similar study with trinexapac-ethyl application for the same species, Marchi et al (2015) observed a reduction of up to 61% at 28 DAA, which does not corroborate the results found by the present research; as for the accumulation of dry mass in the aerial part and in the roots of the St. Augustine grass, the application of the different doses of the growth regulator did not produce any effects. Regarding the aesthetics of the grass, the reduction in inflorescence populations or their absence improves the appearance of the landscape for a long period, besides also reducing the need for lawn mowing.…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…In a similar study with trinexapac-ethyl application for the same species, Marchi et al (2015) observed a reduction of up to 61% at 28 DAA, which does not corroborate the results found by the present research; as for the accumulation of dry mass in the aerial part and in the roots of the St. Augustine grass, the application of the different doses of the growth regulator did not produce any effects. Regarding the aesthetics of the grass, the reduction in inflorescence populations or their absence improves the appearance of the landscape for a long period, besides also reducing the need for lawn mowing.…”
Section: Resultscontrasting
confidence: 97%
“…These results corroborate those found by Marchi et al (2013b) and McCullough et al (2007). JHowever, Marchi et al (2015) observed high levels of phytotoxicity with the single applications of trinexapac-ethyl, at seven days after applications (AAD) in St. Augustine grass; at 56 DAA, when the 452, 678 e 904 g ha -1 doses of the growth regulator were applied, producing slight phytoxicity symptoms. ) up to the 14 DASA (days after the second application), but no effects were observed from 21 DASA.…”
Section: Resultssupporting
confidence: 86%
“…Likewise, Marchi et al (2015) have observed that prohexadione-Ca in doses of 100 and 200 g ha was efficient in reducing growth of St. Augustine grass (Stenotaphrum secundatum), suggesting that the number of mechanical cuts in the lawn may be avoided for a period of up to 119 DAA. As for the total sod grass thickness and without shoots, it was higher when applying the triple sequential dose of 55 g ha -1 of prohexadione-Ca (Table 3).…”
Section: Broadleaf Carpet Grass (Axonopus Compressus)mentioning
confidence: 96%
“…Some research studies have shown that when initial phytotoxicity symptoms by some growth regulators occur, they rapidly dissipate over time without causing greater damage, as observed by Marchi et al (2015) with the application of trinexapac-ethyl, bispyribac-sodium and prohexadione-Ca in the St. Augustine grass (Stenotaphrum secundatum).…”
Section: Broadleaf Carpet Grass (Axonopus Compressus)mentioning
confidence: 99%
See 1 more Smart Citation